INTERNAL DEBT FINANCING AND NIGERIAN ECONOMIC PERFORMANCE (1989-2022) - Ogwo, Pauline Uche; Okoro, Theresa Chidinma (African Journal of Social and Behavioural Sciences, 2024)
The study examined the effect of internal debt financing on Nigerian economic performance for the period 1989-2022. What informed this research was Nigeria's low level of economic growth despite steady increases in the domestic debt stock. The study specifically investigated on effect of Federal Government Bonds, and Treasury Bills on the Nigerian economic performance using the Real Gross Domestic Product as a proxy for economic performance while Money Supply and Interest Rate were used as the control variables. Ex-post facto research design was employed and secondary data were sourced online from the CBN statistical bulletin. Johansson cointegration Test was used to analyse the long-run relationship among the variables in the model while the Vector Error Correction Model was employed to analyse the relationship between the dependent variable and the explanatory variables of the study. Johansson cointegration test results revealed the existence of long-run relationships among the variables of the model. Vector Error Correction Model results revealed that Federal Government Bond as a source of domestic debt financing has significant effect on the Nigerian Real Gross Domestic product for the period in view while Treasury Bill has insignificant effect. Findings further revealed that while money supply and Real Gross Domestic Product are positively related Interest lending Rate and RGDP are negatively related. The research recommends that government should reduce the level of Treasury Bills and increase stock of Federal Government Bond issue in the domestic debt market. Also, government should put in some fiscal measures to maintain a favourable Interest Lending Rate in Nigeria.